Does aerobic capacity play a decisive role in competitive tennis? - Santos, P.; Cabral, V. (2001)
Recent studies involving team sports reported superior aerobic capacity values in elite players comparative to players of inferior competitive level. The purpose of this study was to evaluate the aerobic capacity in two male groups of senior tennis players of different competitive levels: (G1) elite group (n=12), included players with ATP ranking; (G2) non-elite group (n=12), non-professional players. The aerobic capacity was evaluated using the aerobic-anaerobic threshold (Mader et al. 1976), i.e. the running speed at a blood lactate level of 4mmol/l (V4). Capillary blood was taken and analyzed using a YSI-1500L Sport. Training data concerning the 12 weeks previous to the test was also considered. Statistical analysis included the t-test, Pearson correlation and simple linear regression. The significance level was set at 5%. Mean significant differences (t=4,67; p<0,0001) concerning the V4 were found between the groups (G1=3,97±0,28m/s; G2=3,37±0,34m/s). Similar differences were also observed in relation to the specific training concerning such parameters as total training time (TTT) and continuous technical training (CTT). Correlation between CTT and V4 in both groups are high (G1: r=0.83, p<0.0009, r2=69%; G2: r=0.79, p<0.003, r2=63%) and regression coefficients are also of the same magnitude (G1: b =0.83; G2: b =0.79). In conclusion our data evidenced significant differences in aerobic capacity (V4) according to the player`s competitive level. Training anamnesis analysis suggests that a larger TTT and CTT of low intensity might, to some extend, explain the differences in V4. Additionally, the higher values found in the best ranked players within the G1, reinforce the notion that good aerobic conditioning is an essential factor in the professional circuit.